RP-HPLC Estimation of Flavonol Derivatives and Phenolic Acids in Capsicum annuum L. and their Correlation with In Vitro Anti-Inflammatory Activity - Iqbal, Zahra; Ahmad, Ausaf; Haque, Ziyaul; Khan, Mohammed S.; Khan, Mohd S.; Iqbal, Mohammed S. (Current Pharmaceutical Biotechnology, 2020)
Background: Flavonol derivative and phenolic acids derived from the plants function as free radical scavengers, reducing agents, and quenchers for the formation of singlet oxygen. Flavonoids and phenolic constituents also play an important role in various human diseases and disorders primarily through modulation of inflammatory responses. Objective: To estimate the Flavonol Derivatives (FD) and phenolic acids (PA) in Capsicum annuum (CA) and other important phytochemicals having an anti-inflammatory effect. Methods: In the present study, FD and PA were estimated in CA and in vitro anti-inflammatory activity (pilot study) was determined and correlation was established. Results: The results were found to be significant using RP-HPLC. FD and PA were found to be 0.0659±0.0058 and 0.0862±0.0.0134 mg/gram dry weight, respectively. For in vitro anti-inflammatory activity, the inhibition of albumin denaturation and antiproteinase activity was found to be maximum in Quercetin (QE) with 98.230±1.589% and 59.906±1.529%, respectively. Heat-induced hemolysis of erythrocytes was found to be maximum in salicylic acid (SA) (71.830±2.838%). Hypotonicity-induced hemolysis showed significant activity with QE (76.770±3.475%). Lipoxygenase and cyclooxygenase inhibition was found to be maximum in QE with 56.930±4.069% and 61.660±3.135%, respectively. Conclusion: A strong positive correlation of 0.9 was observed between the extract of CA and standard QE and SA against the anti-inflammatory activity. Therefore, the role of FD and PA has been postulated to be an active phytochemical of CA accountable for its anti-inflammatory activity. However further work is desirable to fully elucidate the phytochemicals responsible for their anti-inflammatory activity and to develop better herbal drug formulations.
Keywords: phenolic acids